Konstrukce pneumatik - Sýkora, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Cílem této bakalářské práce je popsat konstrukci pneumatik a porovnat ji u vozidel různých kategorií. V první části je popsán historický vývoj, základní charakteristiky a síly, které působí na kolo vozidla. Dále je zde podrobně rozebrána konstrukce samotné pneumatiky a vysvětlen způsob značení pneumatik. Druhá část práce je zaměřena na rozdíly v konstrukci u jednotlivých kategorií vozidel, jako jsou jednostopá, osobní, nákladní a závodní. Na závěr jsou zmíněny některé alternativy konstrukce a je zde nastíněn budoucí vývoj pneumatik.

The aim of this bachelor thesis is to describe the construction of tires and to compare construction of vehicles of the different categories. The first part describes the historical development, basic characteristics and forces that affect on the wheel of the vehicle. Furthermore, the construction of the tire is analyzed in detail and the method of marking the tires is explained. The second part of the thesis is focused on the differences in tire construction of individual vehicles categories such as single-track, passenger, truck and racing. In conclusion, some construction alternatives are mentioned and the future development of tires is estimated.
Construction of tires
Keywords: pneumatika; konstrukce; značení; vozidla různých kategorií; alternativy konstrukce; tire; construction; marking; vehicles of different categories; construction alternatives